PSIV-6 Engineering Microbes to Develop Novel Direct Fed Microbials as an Alternative to Prophylactic Antibiotic Use in Beef Cattle Production. (12th April 2022) - Neujahr, Alison; Doan, Tien; Kubwimana, Fiacre; Anderson, Christopher; Fernando, Samodha
Abstract: One of the largest animal health related issues in the beef industry is liver abscesses. While the liver is not a significant loss, abscesses formed results in reduced animal performance and carcass yield resulting in reduced feed intake, reduced weight gain, decreased feed efficiency, and decreased carcass dressing percentage. Currently, the most effective method for controlling liver abscesses is the use of antibiotics belonging, to the macrolide family, named Tylosin. Tylosin has been a great resource, however increased use of antibiotics in the beef industry has come under great scrutiny due to emergence of antibiotic resistant bacteria. Therefore, it is critical to develop new methods and technologies to improve beef production while reducing antimicrobial use to feed the growing population. Apart from prophylactic use of antibiotics, a proven strategy for reducing liver abscesses has not been developed. We believe, direct fed microbials (DFM) are promising alternatives to reduce antibiotic use in beef cattle production and to improve animal health, well-being, and productivity. However, many of the strains with the highest potential to reduce antibiotic use are found in non-GRAS (generally accepted as safe) organisms. Additionally, since a single microbe can't inhibit all pathogens, DFM cocktails need to be used to be effective broad spectrum. In this study, we genetically engineered a GRAS approved Bacillus pumilus strain to carry bacteriocins from a non-GRAS approved strain to enhance the capacity of the GRAS approved strain to inhibit liver abscess causing pathogens. We utilized CRISPR/Cas9 system to identify naturally occurring bacterial genes that inhibit pathogen growth and introduced such genes into a GRAS approved strains using transposon mutagenesis and screened for isolates with increased inhibition against pathogens. Such genetically modified bacteria were able to inhibit the pathogens to a greater extent than the wild type B. pumilus strain in in-vitro experiments.